The role of gut microbiota in diabetic peripheral neuropathy rats with cognitive dysfunction - Huang, Wei; Lin, Ziqiang; Sun, Ailing; Deng, JieMin; Manyande, Anne; Xiang, Hongbing; Zhao, Gao Feng; Hong, Qingxiong (Frontiers in Microbiology, 2023)
Owing to advancements in non-invasive magnetic resonance imaging, many studies have repeatedly showed that diabetes affects the central nervous system in the presence of peripheral neuropathy, suggesting a common or interacting pathological mechanism for both complications. We aimed to investigate the role of abnormal gut microbiota in rats with diabetic peripheral neuropathy (DPN) combined with cognitive dysfunction. Glucose-compliant rats with nerve conduction deficits were screened as a successful group of DPN rats. The DPN group was then divided into rats with combined cognitive impairment (CD) and rats with normal cognitive function (NCD) based on the results of the Novel object recognition test. Rat faeces were then collected for 16S rRNA gene sequencing of the intestinal flora. The results revealed that abnormalities in Firmicutes, Ruminococcaceae, Bacteroidia, and Actinobacteria-like microorganisms may induce DPN complicated by cognitive dysfunction.